Designing of Student Dormitories of Syiah Kuala University - Farid Noufaldi (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Unsyiah Student Dormitory is a place for students as a temporary residence during their studies at Unsyiah, so that the presence of this Student Dormitory can help alleviate the burden on students' parents in terms of financing their children's homes during college, not only as a forum for student housing, Student dorms This is also a place for students to learn and be disciplined and far from juvenile delinquency. This student dormitory applies the theme of Tropical Modern which is following the existing climate in Indonesia but still follows modern concepts following the times so that this design theme comes as an idea to solve existing problems.